2015
DOI: 10.3892/ol.2015.3791
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the dual phosphatidylinositol 3-kinase/mammalian target of rapamycin inhibitor NVP-BEZ235 against human Merkel cell carcinoma MKL-1 cells

Abstract: Abstract. Merkel cell carcinoma (MCC) is an aggressive skin cancer with an increasing incidence. Aberrant activation of the phosphatidylinositol-3-kinase (PI3K)/Akt/mammalian target of rapamycin (mTOR) pathway is common in human cancers and has been revealed to play an important function in cell proliferation, metabolism and tumorigenesis. In the present study, NVP-BEZ235, a dual PI3K/mTOR inhibitor, was revealed to be effective in inhibiting proliferation and inducing cell cycle arrest in MKL-1 cells. Additio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 31 publications
1
8
0
Order By: Relevance
“…Consistent with previous reports [ 13 , 14 ], BEZ235 treatment of AQR and H1975DM cells led to G1 cell cycle arrest (Figure 1B ) and reduced cell migration (Figure 1C ), but had no significant effect on apoptosis levels (Figure 1D ). When compared to H1975DM cells, the AQR clones had a reduced G1 block, reduced impedance of cell migration, but no difference in induced apoptosis levels following BEZ235 treatment.…”
Section: Resultssupporting
confidence: 93%
“…Consistent with previous reports [ 13 , 14 ], BEZ235 treatment of AQR and H1975DM cells led to G1 cell cycle arrest (Figure 1B ) and reduced cell migration (Figure 1C ), but had no significant effect on apoptosis levels (Figure 1D ). When compared to H1975DM cells, the AQR clones had a reduced G1 block, reduced impedance of cell migration, but no difference in induced apoptosis levels following BEZ235 treatment.…”
Section: Resultssupporting
confidence: 93%
“…Here, we demonstrate that increased AKT phosphorylation in MCC was reduced significantly in response to myriocin and SKI-II treatment ( Figure 5). Phosphorylation of AKT at S 473 is increased in MCC cell lines in vitro and MCC tumors in situ (Hafner et al, 2012;Lin et al, 2015). Because both inhibitors decreased the extracellular S1P content (Figure 2), it is conceivable that diminished availability of S1P results in reduced basal AKT phosphorylation.…”
Section: Discussionmentioning
confidence: 98%
“…However PI3K pathway upregulation in MCC is independent of MCPyV and provides rationale for the use of PI3K inhibitors, such as ZSTK474 and NVP‐BEZ235, for both virus‐positive and ‐negative MCC . NVP‐BEZ235 inhibits proliferation and induces cell‐cycle arrest in MCC cell lines by upregulating cell‐cycle inhibitors p21 and p27 . Subunits of PI3K, such as p110δ, are detected in 71‐100% of MCC lines and have an unclear contribution to pathway activation .…”
Section: Discussionmentioning
confidence: 99%
“…86,87 NVP-BEZ235 inhibits proliferation and induces cell-cycle arrest in MCC cell lines by upregulating cell-cycle inhibitors p21 and p27. 88 Subunits of PI3K, such as p110δ, are detected in 71-100% of MCC lines and have an unclear contribution to pathway activation. 89 Idelalisib, a selective PI3K-δ inhibitor was used successfully in a patient with stage-IV MCC 90 ; however, further studies demonstrated weak effects in MCC tissues and cell lines.…”
Section: Pi3k-akt-mtor Pathwaymentioning
confidence: 99%